The Urgency of Signature Affixation on the Minutes for Persons with Physical Disabilities as Auction Buyers - Suci Risma Deta; Djumikasih, Djumikasih; Endang Sri Kawuryan (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to analyze the urgency and mechanisms for affixing signatures on auction minutes, particularly for individuals with physical disabilities or limb impairments (physical disabilities) acting as auction buyerss. In the context of Indonesian law, auction minutes constitute an authentic deed requiring a signature as a legal validity condition that grants it full evidentiary strength. However, individuals with limb impairments who may have physical limitations in affixing conventional signatures face challenges in fulfilling this requirement. Therefore, legal reconstruction is crucial to provide alternative valid signatures for individuals with disabilities, such as fingerprints or electronic signatures. This research employs a normative juridical method, referring to relevant legislation and a conceptual approach to analyze legal principles and justice in fulfilling the rights of persons with disabilities. The findings indicate that affixing signatures on auction minutes for individuals with limb impairments is of high urgency to ensure legal certainty and validity. The regulation of alternative valid signatures will ensure that the rights of persons with disabilities are upheld in the legal auction process. Thus, regulatory changes to provide equal access for persons with disabilities in authentic deed transactions are essential for inclusive legal justice and certainty.